Identification and Assessment of Subway Construction Risk: An Integration of AHP and Experts Grading Method. (26th March 2021) - Liu, Junyan; Du, Zijian; Ma, Lixing; Liu, Chao
Abstract : Qing Dao is one of the earliest cities that included the idea of subway construction into the city's transportation plan. However, the construction period of a subway project is long, and the uncertainties caused by the geological conditions and surrounding environments are huge, thus a risk assessment method in subway construction is essential. To ensure the tunnel safety, many researchers have raised different methods for risk assessment. The process of risk assessment can be characterized in three steps: (1) data acquisition; (2) complete the uncertainty model; (3) evaluate the possible risk during the construction. This paper introduces a novel risk assessment method that combines the Analytic Hierarchy Process (AHP) and Experts Grading Method (EGM). The advantage of AHP is that it can quantify the qualitative factors, inspect and reduce the subjective influence to a certain extent, and make the evaluation more scientific. As for the EGM, simplicity and directness are the main characteristics. Assisted by this method, proper measures can be taken to eliminate the potential risk. The integrated method was implemented during the construction of Taishan Road Station of Qingdao Subway to evaluate the potential risk. With the help of this integrated method, the general risk sources during the construction period are well marked and the control measures corresponding to the risk sources are provided.